Approaches to the development of environmental standards for the content of petroleum hydrocarbons and Pb, Cr, Cu, Ni in soils of Greatest Caucasus - Kolesnikov, Sergey; Kuzina, Anna; Minnikova, Tatiana; Akimenko, Yulia; Nevedomaya, Elena; Ter-Micakyants, Tigran; Kazeev, Kamil (Universitas Sebelas Maret, 2022)
The development of tourism and leisure infrastructure results in a continuous increase of anthropogenic impact on soils of wet and dry subtropics of the Greatest Caucasus. It is very important for the region to preserve the sustainable functions of soils and ecosystems, maintain a comfortable life and recreation environment create environmentally friendly agricultural products. It is conducted studies to determine the limits of resistance of soils in wet and dry sub-tropics to priority pollutants, especially petroleum hydrocarbons and heavy metals (Pb, Cr, Cu, Ni). It was found that the soils of wet and dry subtropics for resistance by Pb, Cr, Cu, and Ni are located as follows: south-ern chernozem > typical sod-carbonate soil ≥ brown typical soil ≥ brown carbonate soil = brown leached soil ≥ leached sod-carbonate soil = yellow soil >acid brown forest soil ≥ acid brown forest podzolized soil. In terms of the degree of resistance to oil pollution, studied soils create certain series: brown carbonate ≥ brown typical = sod-carbonate leached ≥ sod-carbonate typical > southern chernozem ≥ yellow soil ≥ brown leached soil > acid brown forest soil = acid brown forest podzolized soil. Heavy metals by ecotoxicity to the soils of wet and dry subtropics from the following series: Cr> Cu ≥ Ni = Pb. Based on the degradation of ecological functions of soils, we offer regional standards of the maximum permissible content of Pb, Cr, Cu, and Ni for the main soils of wet and dry subtropics.